2018
DOI: 10.1007/s00429-018-1733-y
|View full text |Cite
|
Sign up to set email alerts
|

Morphological patterns and spatial probability maps of two defining sulci of the posterior ventrolateral frontal cortex of the human brain: the sulcus diagonalis and the anterior ascending ramus of the lateral fissure

Abstract: The sulcus diagonalis (ds) and the anterior ascending ramus of the lateral fissure (aalf) are two defining sulci of the posterior ventrolateral frontal cortex, which is also known as the anterior language region in the language dominant hemisphere. The aalf extends dorsally from the lateral fissure, separating the pars opercularis from the pars triangularis of the inferior frontal gyrus. The ds, which is a relatively vertical sulcus, is found within the pars opercularis. Given the proximity and similar orienta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 53 publications
1
23
1
Order By: Relevance
“…The aals could be observed in 98.89% of the hemisphere, the hals could be observed in 98.33% of the hemisphere in our study. The results are slightly different from other studies (Sprung-Much and Petrides 2018;Powell et al 2012;Sprung-Much and Petrides 2020;Keller et al 2007). The discrepancy maybe attributed to the great heterogeneity in the brain samples and the differences of sample sizes.…”
Section: Discussioncontrasting
confidence: 99%
“…The aals could be observed in 98.89% of the hemisphere, the hals could be observed in 98.33% of the hemisphere in our study. The results are slightly different from other studies (Sprung-Much and Petrides 2018;Powell et al 2012;Sprung-Much and Petrides 2020;Keller et al 2007). The discrepancy maybe attributed to the great heterogeneity in the brain samples and the differences of sample sizes.…”
Section: Discussioncontrasting
confidence: 99%
“…Sulcal labels in LPFC were based on the most recent parcellation proposed by Petrides (2019; see also Sprung-Much andPetrides, 2018, 2020). In each hemisphere, LPFC sulci in the IFG/ VLPFC and MFG/mid-DLPFC were manually defined at the level of individual participants on both the pial and inflated surfaces (Fig.…”
Section: Sulcal Labelingmentioning
confidence: 99%
“…The French anatomist Gratiolet coined first the terms “pli de passage” (Gratiolet 1854; Parent 2014). Later on, the buried gyri were called annectant, bridging or transition convolutions in the English literature, and also submerged gyrus, or submerged gyral passage in recent publications (Germann et al 2005; Zlatkina and Petrides 2010; Huntgeburth and Petrides 2012; Segal and Petrides 2012; Sprung-Much and Petrides 2018). While these plis de passage seem to appear during the earliest stages of development, which shall lead to regard them as candidates for being a distinctive character of the cortex organization, they did not receive a lot of attention.…”
Section: Plis De Passagementioning
confidence: 99%
“…But dealing comfortably with unusual folding patterns may require an extended vocabulary (Mangin et al 2016). Several very interesting proposals of extended glossary based on regional folding patterns have been proposed (Steinmetz et al 1990; Germann et al 2005; Zlatkina and Petrides 2010; Huntgeburth and Petrides 2012; Segal and Petrides 2012; Plaze et al 2015; Sprung-Much and Petrides 2018; Snyder et al 2019): each reported pattern often corresponds to a specific configuration of the regional plis de passage, leading to alternative connectivity of the regional sulcal roots. This pattern glossary can be used to perform a subdivision of the population relative to the geometry of the cortical morphology.…”
Section: Sulcal Roots and Sulcal Pitsmentioning
confidence: 99%
See 1 more Smart Citation